2023
DOI: 10.1186/s12879-023-08198-9
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of pregnant women exposed to Sotrovimab for the treatment of COVID-19 in the BA.1 Omicron predominant era (PRESTO)

Abstract: Background Sotrovimab, a monoclonal antibody with efficacy against SARS-CoV-2 including certain Omicron variants, has been used in treatment of mild-moderate COVID-19. Limited data exists regarding its use in pregnant women. Methods Electronic medical record review of pregnant COVID-19 patients treated with sotrovimab from 12/30/21 − 1/31/22 (Yale New Haven Health Hospital System [YNHHS]) was performed. Included were pregnant individuals ≥ 12 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Our study suggested that sotrovimab was the drug that achieved the greatest efficacy. Although there were no complications during pregnancy or in the prenatal period for all treatments, as demonstrated by other studies [ 42 , 43 , 44 ], sotrovimab obtained negativization of the infection in less time, especially in the group of pregnant women who were up to date with their vaccination schedule. Contrary to what was reported in a large meta-analysis, it does not depend on vaccination status [ 37 ].…”
Section: Discussionmentioning
confidence: 51%
“…Our study suggested that sotrovimab was the drug that achieved the greatest efficacy. Although there were no complications during pregnancy or in the prenatal period for all treatments, as demonstrated by other studies [ 42 , 43 , 44 ], sotrovimab obtained negativization of the infection in less time, especially in the group of pregnant women who were up to date with their vaccination schedule. Contrary to what was reported in a large meta-analysis, it does not depend on vaccination status [ 37 ].…”
Section: Discussionmentioning
confidence: 51%
“…However, promising preliminary findings suggest that sotrovimab may be an effective and well-tolerated treatment option for pregnant COVID-19 patients. 94 In this study, a cohort of 35 pregnant respondents was investigated to evaluate the utilization of nirmatrelvir-ritonavir during pregnancy. The results revealed that 51.4% of the participants were prescribed this medication, and 34.3% actually took it as per the prescription.…”
Section: Human Immunodeficiency Virus/covid Management During Pregnan...mentioning
confidence: 99%
“…No individuals within the cohort received a booster dose during the study period. 94 The results of a small cohort study that included 30 pregnant and 16 lactating women demonstrated that all participants were immunogenic after receiving COVID-19 messenger RNA. 100…”
Section: Covid-19 Management During Pregnancy--vaccinesmentioning
confidence: 99%